Does Routine Pain Assessment Result in Better Care? - Thomas Hadjistavropoulos; Ying C MacNab; Amanda Lints-Martindale; Ronald Martin; Heather Hadjistavropoulos (Pain Research and Management)
BACKGROUND: Although a variety of national organizations such as the Canadian Pain Society, the American Pain Society and the Joint Commission on Accreditation of Health Care Organizations have advanced the idea that pain should be assessed on a routine basis, there is little evidence that systematic pain assessment information is used routinely by clinicians even when it is readily available.